An efficient PDE framework for satellite image classification - S. Bettahar; A. Boudghene Stambouli (Revue des Énergies Renouvelables, 2010)
In this paper, we present a method based on coupling between shock filter and diffusion process for image restoration. This method smoothes homogeneous part of the image, while it enhances edges efficiently. This selective smoothing propriety is used as a pretreatment step for an efficient classification of infrared satellite images, in order to cluster the solar field.